Service Quality Improvement through ODI: A Case Study of Prem Mansion, Bangkok - Keyuraphan, Sarinee; Preudhikulpradab, PhD, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
Abstract This study aims to determine the initial impact of organization development intervention on willingness, problem resolution, time management, and communication skills of employees to enhance service quality and customer satisfaction. Consequently, the work is expected to benefit the organization of Prem Mansion itself in terms of better reputation and trust resulting from the improved service quality. The research covers three phases – Pre-ODI, ODI implementation, and Post- ODI. The first stage is to seek to understand the current situation, including a short survey to seek satisfaction level of both customer and employee sides. The second phase, ODI implementation is designed to solve problems directly to the point. The post-ODI phase allows the comparison of the results after the intervention to those seen before doing organization development intervention using by Wilcoxon Signed Ranks Test. Comparing the results from pre- and post-interventions of both employees’ and customers’ sides, an obvious difference can be seen. After the intervention, the employees have realized they are lack of certain skills; therefore evaluate themselves lower than pre-intervention period. On the other hand, there has been an initial impact on customer satisfaction in the aspects of the willingness to provide service, problem resolution, time management, and communication skills have risen. Keywords: service quality, customer satisfaction, willingness, problem resolution, time management, communication skill